KETAHANAN LIMA JENIS KAYU TERHADAP BEBERAPA JAMUR PERUSAK KAYU - Sihati suprapti; djarwanto djarwanto; hudiansyah hudiansyah (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
The resistance of five wood species originated frim west java were evaluated using DIN52176-modified standard.wood sample were divided into two groups radially,namely outer andInner parts of log.results showed that bengkal wood(nauclea orientalis L.). mindi (melia dubiacav.)and biantaro(cerbera sp.) were moderately resistant against several fungal attack (class III).whereas .jaran (lannea coromandclica merr.) and waru (hibiscus tiliaceus L.)were not resistant (class IV). Weigtht loss percentage of the inner part of log was lower than that of the auter part.the highest weight los was encountered on the inner part of jaran exposed tocorioulus versicolor culture (52.26%).while the lowest was found on the inner part of waru exposed to pycnoporus sanguincus HHB-8149 (0.53%) the most severe attacks were perfomed by corilus versicolor.followed by pycnoporus sanguineus HHB-324,tyroyces palustri,and polyporus sp.